SAVIPS: Uma Infraestrutura Veicular Autônoma em Pequena Escala para ADAS - Coelho, Alexsandro; Silva-Filho, Abel G. (Anais do Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas Veiculares (SSV); 2024: Anais do I Workshop Latinoamericano de Dependabilidade e Segurança em Sistemas VeicularesDO - 10.5753/ssv.2024.32622, 2024)
Traffic accidents are a leading cause of global mor tality, with 1.35 million fatalities and 50 million injuries annually, mainly due to human error, such as recklessness and alcohol use. This paper presents SAVIPS, a small-scale autonomous vehicle infrastructure to test Advanced Driver Assistance Systems (ADAS), enabling the validation of safety features without the costs and risks of full-scale vehicle testing. The infrastructure integrates speed sensors, cameras, and communication modules for real-time evaluation. Despite limitations in results, such as 14-hour battery life and ±3 degrees lateral control accuracy, they validate component efficiency. Intra-vehicle communication used 0.309% of the CAN bus capacity, and inter-vehicle com munication showed high reliability, with one packet lost per 250 transmitted. These results highlight the potential of scaled models in advancing autonomous technologies and improving road safety.